Model Laboratorium Pengaruh Variasi Sudut Arah Pengaman Pilar Terhadap Kedalaman Gerusan Lokal Pada Jembatan Degan Pilar Cylinder Grouped (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bridge pillars placed on meander river experience hydrodynamic flow and helecoidal force. Those force will cause local scour on pillars and pillar protectors. Pillar protectors with specified angle is expected to be able to minimize the magnitude of scouring on pillars. Laboratory model with grouped cylinder type pillars with three variation of angle of curtain type pillars protector (Î¸1, Î¸2, Î¸3) are used to obsorved the phenomenon of scouring that occured on meander river. Kampar sand with grain size of d35 = 0,247 mm, d50 = 0,298 mm, d65 = 0,352 mm and Gs = 2,64 are used as the base for the bed of the channel. Three type of subcritic flow with froude number ranged from o,464-0,698 and yield the reynolds number occured on Fr1-Fr3 at 1658,416 thus classified as transition flow while 3081,683 and 4381,188 are classified as turbulence flow. Shield graphic showed that grain gradation used in this research is located one moving zone. The ratio of scouring depth (ds/b) of pillars protectors is highest 2,4 that occured on Fr3 Î¸2 and Fr1 Î¸3 while on the pillars is occured on Fr2 Î¸2 at 1,9. The results of sediment transport analysis proved that with the in crease in froude number used the bigger the size of the grain transported.Key word : local scouring, grouped cylinder pillar, angle of pillars protector, curtain type pillars protectot, depth ratio.